2014
DOI: 10.1080/02701960.2014.907158
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions of a Community-Based Service-Learning Project Related to Aging in Place

Abstract: This article describes a service-learning project that was designed to help undergraduate health professions students understand the complexities related to aging in place. The service-learning project also incorporated a research component to expose the students to the research process. Students' reflections regarding the benefits that they derived from the experience suggest that they value learning about older adults through one-on-one interactions more than they value the opportunity to participate in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…In this sense, intergenerational experiences may help students learn about older adults, confront stereotypes about aging, and consider working with this population (Oakes and Sheehan, 2014). Engaging students in intergenerational service-learning (SL) experiences is a means of raising students' interest in the aging population and making learning experiences more meaningful (Oakes and Sheehan, 2014;Andreoletti and Oward, 2016;Yeung et al, 2019). The value of students gaining direct personal experience working with or providing services to older adults has long been recognized (Zucchero, 2010;Chen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, intergenerational experiences may help students learn about older adults, confront stereotypes about aging, and consider working with this population (Oakes and Sheehan, 2014). Engaging students in intergenerational service-learning (SL) experiences is a means of raising students' interest in the aging population and making learning experiences more meaningful (Oakes and Sheehan, 2014;Andreoletti and Oward, 2016;Yeung et al, 2019). The value of students gaining direct personal experience working with or providing services to older adults has long been recognized (Zucchero, 2010;Chen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Research in the community may enhance student motivation, particularly if they perceive a positive contribution to the people being served (Goto & Bianco-Simeral, 2009). By participating in community research within a CURE, preservice music teachers may experience changes in worldviews (Riley et al, 2006), enhanced cultural awareness and appreciation (Niven et al, 2013;Oakes & Sheehan, 2014), and improved understanding of practical difficulties and rewards of conducting research (Smith & McCaslin, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, students have found that their service learning experiences serve as a bridge from their education to direct practice with community partners (Cress et al, 2005). Service learning in these settings can improve students' attitudes and knowledge about older adults and address common stereotypes about aging (Krout et al, 2010;Oakes & Sheehan, 2014).…”
Section: Service Learning Within Independent Living Settingsmentioning
confidence: 99%
“…This approach to learning allows students to gain real-world practice experience while also providing a necessary community service (Hyde & Meyer, 2004;Miller et al, 2017). The service learning model includes some common elements that are necessary to achieve the goals of improving student education and serving communities: programs and activities are developed in collaboration with communities; the services provided respond to community needs; students typically lead activities with faculty and staff oversight; and students engage in intentional reflection on their experience (Gibson et al, 2011;Oakes & Sheehan, 2014;Seif et al, 2014;Seifer, 1998). Traditional settings for service learning activities include agencies and clinics in the community or within facilities housed on a college campus (Krout & Pogorzala, 2002).…”
mentioning
confidence: 99%